A NEOLITHIC CARVED STONE BALL FROM SCOTLAND ACQUIRED BY SIR JOHN LUBBOCK (LORD AVEBURY), WITH COMMENTS ON THE SCOTTISH CONNECTIONS OF LUBBOCK AND HIS COLLECTION. (September 2015) - Saville, Alan
Abstract : A previously unpublished Neolithic carved stone ball from Aberdeenshire, Scotland, is described. This intricately decorated object formed part of the collection of Sir John Lubbock (Lord Avebury) and is now housed at the Bromley Museum, Orpington, Greater London. The intrinsic importance of this ball is discussed and its interest is enhanced by the details of its collection history. The acquisition of other items from Scotland in the Avebury Collection at Bromley Museum is put in the context of Lubbock's contacts and visits to Scotland. RÉSUMÉ: Cet article présente une boule de pierre sculptée datant du néolithique, découverte à Aberdeen, en Écosse. Cette boule à la décoration fouillée, encore jamais décrite dans une publication, faisait partie de la collection de Sir John Lubbock (Lord Avebury) et se trouve aujourd'hui au musée de Bromley, à Orpington, dans le Grand Londres. L'article examine l'importance intrinsèque de cette boule dont l'intérêt est accentué par les détails de l'histoire de sa collection. L'acquisition d'autres objets d'origine écossaise figurant dans la collection Avebury conservée au musée de Bromley est resituée dans le contexte des contacts de Lubbock avec l'Écosse et de ses visites dans ce pays. ZUSAMMENFASSUNG: Beschrieben wird ein bisher unveröffentlichter neolithischer Carved Stone Ball (gemeißelte Steinkugel) aus Aberdeenshire in Schottland. Dieses kunstvoll verzierte Objekt, das der Sammlung von Sir John Lubbock (Lord Avebury) angehörte, befindet sich jetzt im Bromley Museum, Orpington, einem Außenbezirk von London. Die zentrale Bedeutung dieser Kugel wird besprochen und von besonderem Interesse sind dabei auch die Einzelheiten ihrer Sammlungsgeschichte. Der Erwerb anderer Stücke von Schottland aus der Avebury Sammlung im Bromley Museum wird in den Kontext von Lubbocks Kontakten und Besuchen in Schottland gestellt.